Trabalho e subjetividade: uma análise da aposentadoria na velhice - Soares, Katiúscia Ribeiro de Almeida (2020)
The research has as its fundamental premise the work conception of as an ontological and historical category. The starting point was this conception to understand the particularity of retirement for elderly individuals in the current context of capital security, marked by the crisis in its structural base and by the revision of neoliberal policies. These markers affected, substantially, all spheres of workers' lives, both with respect to social and subjective aspects. The study aimed to identify, analyze and understand the meanings that retired workers receive the social benefits present in the relationships between work, subjectivity, retirement and old age in contemporary times. A survey is of the basic type of qualitative character. It is based on the Historical Dialectical Materialism method. Information and evidence, sources and testimonies were collected through the field diary and semi-structured interviews. As the time the interviews were carried out with six participants, three males and three females, aged 64 to 85 years old, retired after a long economically active life in the world of work. Proceed with a triangulation of information and sources. Objective-to apprehend or object of investigation, taking into account its real movement, marked by contradiction and located within a historical historical, characterized by the capital crisis. To do this, establish a dialogue with authors who approach this theoretical-methodological framework in the field of Social Sciences, Social Psychology at Work, Historical-Cultural Psychology and Social Work. The results of the investigation are that either the phenomenon of retirement in old age is conceived as the place of leisure, of having nothing to do, of unproductivity and disability, in which an association was established with the arrival of death. Old age retirement is also sent as freedom and personal fulfillment. It is noteworthy that it is permeated by the denial of old age, and that the forms of work exercised throughout life, as it is experienced by the subjects, reverberate in the experience of old age retirement.